Stress-strain characteristics of concrete containing quarry rock dust as partial replacement of sand - Charles K. Kankam; Bismark K. Meisuh; Gnida Sossou; Thomas K. Buabin (Case Studies in Construction Materials, 2017)
The paper presents results of study on concrete using quarry dust to replace sand at levels of 0%, 25%, and 100% by weight. Design mixes were prepared to achieve concrete grades C25, C30, C35, C40 and C45 for each of the three replacement levels. Prismatic specimens were prepared to study the stress-strain behaviour of the concrete. It was observed that the stress-strain curves were similar for all sand replacement levels and that concrete with 100% quarry dust had the maximum strain values. The results of the study showed that for all concrete grades, 25% sand replacement level gave higher (7.9%) modulus of elasticity (MoE) while 100% sand replacement level gave lower (8.6%) MoE relative to 0% sand replacement level. The estimated MoE was compared with values obtained from the formulas proposed by the BS, ACI and IS for estimating the MoE using the compressive strength of concrete. It was found that blending sand and quarry dust produces concrete of enhanced mechanical properties.